Act early to prevent infections and save lives: causal impact of diagnostic efficiency on the COVID-19 pandemic - Chen, Simiao; Jin, Zhangfeng; Vollmer, Sebastian; Bärnighausen, Till; Bloom, David E. (GLO discussion paper, 2021)
This paper examines the causal impact of diagnostic efficiency on the COVID-19 pandemic in China. Using an instrumental variable approach, we show that a 1-day decrease in the time taken to confirm the first case in a city publicly led to 9.4% and 12.7% reductions in COVID-19 prevalence and mortality over the subsequent six months, respectively. The impact was larger for cities that are farther from the COVID-19 epicenter, are exposed to less migration, have more responsive public health systems, and have higher-capacity utilization of health systems. Social distancing and a less burdened health system are likely underlying mechanisms.